Gene-controlled resistance to aromatic hydrocarbons Neurospora crassa and its relationship to the inhibition by L-sarbose - S. G. Georgeopoulos; A. Kappas; B. Macris (Fungal Genetics Reports, 1966)
Resistance to aromatic hydrocarbons